MODIFICATION OF AMBERLITE IRA 400 (CL-) BY INCORPORATING ALIZARIN S AND SODIUM MORPHOLYLDITHIOCARBAMATE (MORDTC) RESPECTIVELY - Guerra, M.; Díaz, C.; Martínez, N.; Autié, M.; Pomes, R.; Bello, E.; Niubó, E.; Rodríguez, J.; Cao, R.; Melchor, K. (Tecnociencia, 2003)
A chelating sorbent was obtained by incorporating Alizarin S and Sodium Morpholyldithiocarbamate (MorDTC) respectively in Amberlite IRA 400 (Cl-). Structural characteristics were studied by X-Ray Powder Diffraction (XRD), Optical Microscopy (OM), Differential Scanning Calorimetry (DSC) and Adsorption Techniques. The pH of optimal retention pH of MorDTC in Amberlite IRA 400 (Cl-) was obtained (pH 8-9). For Alizarin S an optimal retention is achieved even at pH 1-2. The sorption capacity of the resin without modification is 0.575 mmol g-1 .